TEOLOGI PEMBEBASAN PEREMPUAN: KAJIAN ATAS PEMIKIRAN ASGHAR ALI ENGINEER TENTANG ISU GENDER - Daud, Fathonah K.; Fauziah, Nadia Rizky; Rizqiyyah, Siti (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2023)
This article examines Asghar Ali Engineer's thoughts on women's liberation theology. This is mainly about the method of interpreting Islamic sacred texts. This article was collected from a literature review, then described and analyzed using gender theory. The results of this research show that Asghar's feminist spirit is very strong when reading and interpreting Islamic sacred texts. This cannot be separated from the influence of the science he mastered, including his plural life experience in India, which gave birth to a humanist method of interpretation. The Islamic portrait has shown the existence of gender justice according to Ali Asghar Engineer's perspective, they are both servants of Allah whose process of events is of the same type. The only difference lies in how they carry out their life functions as caliphs on earth, whether they become devout servants or not. Criticism of classical fiqh was raised because it was considered discriminatory against women, so Ali Asghar offered a reconstruction of feminist fiqh for a more just life.